Impact of Endothelial Microparticles on Coagulation, Inflammation, and Angiogenesis in Age-Related Vascular Diseases - Margaret Markiewicz; Erin Richard; Natalia Marks; Anna Ludwicka-Bradley (Journal of Aging Research)
Endothelial microparticles (EMPs) are complex vesicular structures that originate from plasma membranes of activated or apoptotic endothelial cells. EMPs play a significant role in vascular function by altering the processes of inflammation, coagulation, and angiogenesis, and they are key players in the pathogenesis of several vascular diseases. Circulating EMPs are increased in many age-related vascular diseases such as coronary artery disease, peripheral vascular disease, cerebral ischemia, and congestive heart failure. Their elevation in plasma has been considered as both a biomarker and bioactive effector of vascular damage and a target for vascular diseases. This review focuses on the pleiotropic roles of EMPs and the mechanisms that trigger their formation, particularly the involvement of decreased estrogen levels, thrombin, and PAI-1 as major factors that induce EMPs in age-related vascular diseases.